Pengaruh Promosi Dan Merek Terhadap Keputusan Pembelian Di Home Industry Makanan Ringan Comet “Si Rawing” - Sopiyudin, Lutfi; Herdiyanti, Herdiyanti; Arifah, Alfin Nur (Magister Manajemen Universitas Wisnuwardhana, 2025)
Purchase Decisions in the Home Industry of Snack Products “Comet Si Rawing” This research adopts a quantitative approach with a survey method to examine the influence of promotion and brand on consumer purchase decisions in the context of a small-scale snack manufacturing business. A total of 100 respondents were selected using purposive sampling. Data were obtained through questionnaires, observations, and documentation, and analyzed using statistical techniques with SPSS version 27. The findings reveal that promotion exerts a positive and significant influence on purchase decisions. Similarly, brand also demonstrates a positive and significant impact on purchase decisions. These results underscore the importance of implementing effective promotional strategies and maintaining a strong brand image to enhance consumer interest and purchasing behavior